2023
DOI: 10.3390/children10050870
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Urinary Hepcidin Level and Hypoferremia in Infants with Febrile Urinary Tract Infection: A Prospective Cohort Study

Abstract: To evaluate the kinetics of serum and urinary hepcidin levels along with anemia-related parameters during the infection course of infants with febrile urinary tract infection (UTI), we enrolled febrile infants aged one to four months in this prospective study. Febrile patients with UTI were allocated into Escherichia coli (E. coli) or non-E. coli groups according to urine culture results. Septic workup, blood hepcidin, iron profile, urinalysis, and urinary hepcidin–creatinine ratio were collected upon admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Monitoring Hb levels in febrile children can provide valuable insights into the severity of the illness and guide appropriate management strategies [7,24,28]. We have also observed lower Hb and higher CRP levels in children with bacteremia [7], urinary tract infection [29], or Kawasaki disease in our previous studies [24,28]. The combination of Hb and CRP can be an effective diagnostic approach for these cases [24,30].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Monitoring Hb levels in febrile children can provide valuable insights into the severity of the illness and guide appropriate management strategies [7,24,28]. We have also observed lower Hb and higher CRP levels in children with bacteremia [7], urinary tract infection [29], or Kawasaki disease in our previous studies [24,28]. The combination of Hb and CRP can be an effective diagnostic approach for these cases [24,30].…”
Section: Introductionmentioning
confidence: 55%
“…Sepsis or bacteremia can lead to a decrease in serum iron levels and is associated with elevated levels of hepcidin [ 54 ]. Thus, hepcidin has proven to be a valuable biomarker for evaluating the prognosis and outcome of critically ill patients [ 29 , 45 , 55 , 56 ]. Michels et al further demonstrated that inducing hepcidin during pneumonia is crucial in curbing bacterial spread by restricting extracellular iron availability [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several categories of iron metabolism markers have already been measured for prognostic purposes in children with febrile urinary tract infection and in children after intensive chemotherapy for acute leukemias or undergoing hematopoietic cell transplantation. So, parameters determining functional and storage iron pool (iron, total iron-binding capacity, transferrin, ferritin, ferritin heavy and light chain), proteins contributing to the absorption of iron and its release from tissues stores (hepcidin, soluble ferroportin-1 and soluble hemojuvelin) and proteins determining the erythropoietic activity of the bone marrow (erythropoietin, erythroferrone, and soluble transferrin receptor) [61,62] could be considered for future research also in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The urine hepcidin/creatinine ratio correlates positively with SF and negatively with the zinc protoporphyrin-to-heme ratio in ELGAN [100]. Hepcidin is affected by RBC transfusions, ESA administration, iron treatment, infection, and inflammation [100,101,[104][105][106][107]. There are no data on hepcidin's sensitivity as a biomarker of brain dysfunction in perinatal ID.…”
Section: Hepcidinmentioning
confidence: 99%